Profitability in soybean production on the Bom Jardim Lagoano farm with on-farm biological management (Research, Society and Development, 2022)
The average productivity of the soybean crop increased by about 10% in 2012 and 2022. However, profitability was harmed due to the evolution of soybean production costs in Brazil. The use of biological inputs produced on farm has proved to be an alternative in reducing costs. This study presents, in an unprecedented way, data on cost, production and profitability over twelve consecutive annual crops (2010-2022) in soybean cultivation with the application of biologicals, as part of the management of a NUPIO established at the Fazenda “Bom Jardim Lagoano” and aims to discuss the advantages of its use in the context of Brazilian agribusiness. Six harvests with conventional management (2010/2011-2015/2016) and six harvests with biological management (2016/2017-2021/2022) were conducted, and a completely randomized design was adopted. For both managements, the cost of production, productivity and profitability of the farm in bags ha-1. Farm data were compared with data obtained by CONAB in the Rio Verde-GO micro-region. The results show that on the farm, handling with biological inputs produced on farm reduced production costs (58.6%), with an increase in productivity (13%) and profitability (175%) of the soybean crop. The farm proved to be efficient in terms of productivity in relation to the RIO VERDE-GO micro-region, with a reduction in production cost of 11.58% and an increase in profitability of 83%. Management with biological inputs produced “on farm” is an excellent alternative for production in Brazil, provided that the standards for production, quality control and application of biologicals are met.